WHEN TEACHING IS MEANINGFUL BUT LEARNING FEELS OTHERWISE: TEACHER–STUDENT CRITERIA MISALIGNMENT IN INDONESIAN EFL CLASSROOMS - Mauly Halwat Hikmat (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Meaningful learning has increasingly been positioned as a core objective in contemporary English as a Foreign Language (EFL) instruction, particularly in classroom settings where learning is expected to support both academic achievement and authentic language use. However, teachers and students may share a commitment to meaningful learning while relying on different criteria to evaluate its presence. This study examines the extent of perceptual alignment between EFL teachers and students in Indonesian secondary classrooms and investigates the evaluative criteria employed by each group in assessing meaningful learning. Using a convergent mixed-methods design, quantitative and qualitative data were collected concurrently and analysed separately before being integrated at the interpretation stage. The findings indicate that while both groups endorsed meaningful learning as an important instructional goal, their evaluations diverged consistently across all dimensions examined. Statistically significant perceptual differences were found across all dimensions of meaningful learning, with moderate to large effect sizes; teachers consistently reported higher mean scores than students. The study reveals that teachers primarily relied on pedagogical, curricular, and assessment-based indicators, whereas students emphasized experiential, affective, and relevance-based criteria. This criteria gap provides an empirical explanation for the perceptual misalignment observed in EFL classrooms, whereby meaningful learning may be pedagogically intended but not fully experienced as meaningful by learners. The study concludes that meaningful learning is not solely determined by instructional design, but emerges through the interaction between pedagogical intentions and learner evaluations.